2015
DOI: 10.1016/j.bandl.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Word tones cueing morphosyntactic structure: Neuroanatomical substrates and activation time-course assessed by EEG and fMRI

Abstract: Previous studies distinguish between right hemisphere-dominant processing of prosodic/tonal information and left-hemispheric modulation of grammatical information as well as lexical tones. Swedish word accents offer a prime testing ground to better understand this division. Although similar to lexical tones, word accents are determined by words' morphosyntactic structure, which enables listeners to use the tone at the beginning of a word to predict its grammatical ending. We recorded electrophysiological and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
56
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 45 publications
7
56
2
Order By: Relevance
“…For Swedish, it has been suggested that tones on word stems (“word accents”) are used as cues to pre-activate upcoming suffixes (Roll et al. 2015). Suffixes that are invalidly cued by an incorrect tone have been seen to increase response times and lead to a P600 reprocessing effect in event-related potential (ERP) studies (Roll et al.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For Swedish, it has been suggested that tones on word stems (“word accents”) are used as cues to pre-activate upcoming suffixes (Roll et al. 2015). Suffixes that are invalidly cued by an incorrect tone have been seen to increase response times and lead to a P600 reprocessing effect in event-related potential (ERP) studies (Roll et al.…”
Section: Introductionmentioning
confidence: 99%
“…2013; Roll 2015; Roll et al. 2015). However, it is unclear whether this tone-morphology interaction is based on a direct association between tones and suffixes in the brain, independent of their association with lexical word stems, or whether the tone-suffix association is dependent on and tied to whole word forms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations